English Compound Words Used in The Jakarta Post’s Health Column on Third Week of June 2020 - Sisvinda, Felix Stefani (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2022)
This study aims to describe the orthographic features, word formation and the meaning of compound words related to COVID-19 pandemics used in The Jakarta Post’s Health Column Article on Third Week of June 2020. There are three research questions in this study: (1) What are orthographic features found in the compound words, (2) What are the type of compound words and their lexical categories, and (3) How do the compound words create meaning. To answer the research question, the writer use the theory of morphology and semantics. The findings showed there are 34 compound words in The Jakarta Post’s Health Column on the third week of June 2020. The compound words found in this study are written mostly in one word. Then, the rest of compound words are written with a hyphen, and separately in two or three words. Based on the type of compound words, there are 82.35% compound noun, 11.75% compound adjective, and 5.9% compound verb. The most dominant lexical category is from compound nouns which are Noun + Noun and Adjective + Noun. Based on the meaning of compound words, there are 85.3% endocentric compounds and 14.7% exocentric compounds.